2010
DOI: 10.1364/ao.49.000d12
|View full text |Cite
|
Sign up to set email alerts
|

Improved illumination system for spatial coherence control

Abstract: An improved illumination system is proposed for creating a temporally coherent and spatially incoherent extended source to be used for spatial coherence control and reconstruction of a coherent hologram. Taking into account the fact that a rotating ground glass does not behave as an ideal Lambertian diffuser, the new illumination system tailors the directivity of the scattered lights to direct the lights efficiently into an interferometer so that a spatial coherence function can be better controlled and detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…For biomedical optics applications the use of infrared light is preferable as it penetrates deeper in tissue [90], which then requires the development of highresolution infrared cameras. For frequency-domain FF-OCT operation [91], tunable sources and fs sources that can reveal the spectral interference images in a short time will be helpful.Finally, it should be mentioned that spatial coherence effects in other related fields such as interferometry in general, holography, surface profiling and other applications has been an active field of research during the last two decades [92][93][94][95][96][97]. The group at Saratov University has been studying longitudinal spatial coherence extensively [98][99][100][101] …”
Section: Conclusion and Future Trendsmentioning
confidence: 99%
“…For biomedical optics applications the use of infrared light is preferable as it penetrates deeper in tissue [90], which then requires the development of highresolution infrared cameras. For frequency-domain FF-OCT operation [91], tunable sources and fs sources that can reveal the spectral interference images in a short time will be helpful.Finally, it should be mentioned that spatial coherence effects in other related fields such as interferometry in general, holography, surface profiling and other applications has been an active field of research during the last two decades [92][93][94][95][96][97]. The group at Saratov University has been studying longitudinal spatial coherence extensively [98][99][100][101] …”
Section: Conclusion and Future Trendsmentioning
confidence: 99%
“…It has been experimentally demonstrated that longitudinal coherence length of light of a thermal source can be determined by its angular spectrum 6 . The methods applied the longitudinal spatial coherence determined by broad angular spectrum of quasi-monochromatic light source to surface profilometry are being developed 10,11 . The problem of restriction of coherence properties of a light field in longitudinal direction caused by its broad angular spectrum arises and is being investigated in so-called ghost imaging methods 12,13 .…”
Section: Longitudinal Spatial Coherence Of the Optical Field And Its mentioning
confidence: 99%
“…The first scheme with a convergent lens in the input of Michelson interferometer (Fig.4a) at 0 S z is used in the methods applied the spatial coherence to profilometry of surfaces 10,11 . In our experiment we use an interferometer with a lens in its output (see optical scheme in Fig.4b) 6,21 because this scheme makes it possible to investigate the longitudinal spatial coherence in the region near to the focal plane of a lens.…”
Section: Longitudinal Coherence In Image Spacementioning
confidence: 99%
“…One of the major problems in precision interferometers is the coherent noise or fringe noise, which arises from the spurious interference of lights reflected from the surfaces of the imperfectly transmissive optical components, as well as light scattered by the dust and defects on optical surfaces [1]. Even though all optical components placed in the path of light are coated and tilted to prevent spurious interference, coherent noise due to spurious reflection cannot be avoided completely [2] and results in serious phase error and low measurement accuracy [3].…”
Section: Introductionmentioning
confidence: 99%